Pasteurella multocida and Bordetella bronchiseptica infections in rabbits. - Deeb, B J (1990)
The natural history of infection with Pasteurella multocida and Bordetella bronchiseptica in domestic rabbits was studied prospectively at a commercial rabbitry. At weaning, about 25% of rabbits had nasal infections with P. multocida and 75% had infections with B. bronchiseptica. Infection of weanling rabbits paralleled nasal infections of their dams. The proportion of rabbits with both infections increased with age. At 2 to 4 months old, about 50% of rabbits with P. multocida or P. multocida and B. bronchiseptica infections had upper respiratory disease (URD), whereas rabbits with B. bronchiseptica infection had no disease. In rabbits about 10 months old, 75% with P. multocida or P. multocida and B. bronchiseptica infections had URD, whereas virtually none with B. bronchiseptica infection had disease. Disease of the nares, paranasal sinuses, middle ears, and lungs was associated with P. multocida and not B. bronchiseptica infection. In adult rabbits with nasal P. multocida infection, with or without signs of URD, about 80% had concurrent infection of the paranasal sinuses and middle ears and 20% had infection of the bronchi and lungs. In rabbits without nasal P. multocida infection, 20 to 35% had P. multocida infection of the paranasal sinuses and middle ears. Weanling rabbits with and without P. multocida infection had similar immunoglobulin G (IgG) levels. In rabbits observed prospectively, the only antibody differences between those transiently and persistently infected with P. multocida were a diminished IgA response in nasal lavages and an earlier IgM response in sera of transiently infected rabbits. IgG levels increased with the duration of infection. There was no relationship between immunoglobulin levels and freedom from P. multocida infection.